The Effect of Climatic and Hydrologic Criteria Changes on Desertification in Mehran Plain - Kamran Karimi; Reyhaneh Masoudi; Sara Nakhaee Nejad Fard; Behnaz Zehtabian (مدیریت بیابان, 2014)
In this study, IMDPA model was used to assess desertification phenomena regarding the importance of agriculture in Mehran plain. Climatic and hydrologic criteria were selected to consider over two periods 2002-2007 and 2008-2012. Two climatic indices (Precipitation index and SPI) and three hydrologic indices (Groundwater level depletion, EC and TDS) were chosen to quantify climatic and hydrologic criteria, with which desertification intensity was calculated and classified for mapping by Arc GIS 9.03. Desertification intensity was classified in four classes including negligible and low, medium, high and very high. According to the results, among studied indices, SPI with the values of 2.45 and 2.78 and the groundwater level depletion with the values of 3.68 and 3.97 were the most effective factors. The results of analysis indicated that drought, decreased precipitation and groundwater level depletion cause an increase in desertification in Mehran Plain.